Development of an interlaced-crossfiring geometry for proton grid therapy. (2nd November 2017) - Henry, Thomas; Bassler, Niels; Ureba, Ana; Tsubouchi, Toshiro; Valdman, Alexander; Siegbahn, Albert
Abstract: Background: Grid therapy has in the past normally been performed with single field photon-beam grids. In this work, we evaluated a method to deliver grid therapy based on interlacing and crossfiring grids of mm-wide proton beamlets over a target volume, by Monte Carlo simulations. Material and methods: Dose profiles for single mm-wide proton beamlets (1, 2 and 3 mm FWHM) in water were simulated with the Monte Carlo code TOPAS. Thereafter, grids of proton beamlets were directed toward a cubic target volume, located at the center of a water tank. The aim was to deliver a nearly homogeneous dose to the target, while creating high dose heterogeneity in the normal tissue, i.e., high gradients between valley and peak doses in the grids, down to the close vicinity of the target. Results: The relative increase of the beam width with depth was largest for the smallest beams (+6.9 mm for 1 mm wide and 150 MeV proton beamlets). Satisfying dose coverage of the cubic target volume ( σ < ±5%) was obtained with the interlaced-crossfiring setup, while keeping the grid pattern of the dose distribution down to the target (valley-to-peak dose ratio <0.5 less than 1 cm before the target). Center-to-center distances around 7–8 mm between the beams were found to give the best compromise between target dose homogeneity and low peak doses outside of the target. Conclusions: A nearly homogeneous dose distribution can be obtained in a target volume by crossfiring grids of mm-wide proton-beamlets, while maintaining the grid pattern of the dose distribution at large depths in the normal tissue, close to the target volume. We expect that the use of this method will increase the tumor control probability and improve the normal tissue sparing in grid therapy.